Different effects of alpine woody plant expansion on domestic and wild ungulates. (28th February 2019) - Espunyes, Johan; Lurgi, Miguel; Büntgen, Ulf; Bartolomé, Jordi; Calleja, Juan Antonio; Gálvez‐Cerón, Arturo; Peñuelas, Josep; Claramunt-López, Bernat; Serrano, Emmanuel
Abstract: Changes in land‐use and climate affect the distribution and diversity of plant and animal species at different spatiotemporal scales. The extent to which species‐specific phenotypic plasticity and biotic interactions mediate organismal adaptation to changing environments, however, remains poorly understood. Woody plant expansion is threatening the extent of alpine grasslands worldwide, and evaluating and predicting its effects on herbivores is of crucial importance. Here, we explore the impact of shrubification on the feeding efficiency of Pyrenean chamois ( Rupicapra p. pyrenaica ), as well as on the three most abundant coexisting domestic ungulate species: cattle, sheep and horses. We use observational diet composition from May to October and model different scenarios of vegetation availability where shrubland and woodland proliferate at the expense of grassland. We then predicted if the four ungulate species could efficiently utilize their food landscapes with their current dietary specificities measuring their niche breath in each scenario. We observed that the wild counterpart, due to a higher trophic plasticity, is less disturbed by shrubification compared to livestock, which rely primarily on herbaceous plants and will be affected 3.6 times more. Our results suggest that mixed feeders, such as chamois, could benefit from fallow landscapes, and that mountain farmers are at a growing economic risk worldwide due to changing land‐use practices and climate conditions. Abstract : Climatic and land‐use changes are leading to shrub expansion in alpine grasslands. In this work, we address whether wild and domestic herbivores under varying conditions of resource availability will be able to use efficiently their foraging landscape. We found that "shrubification" affects herbivores differently depending on their feeding preferences and plasticity. Mixed feeders will manage better in fallow landscapes but free‐ranging livestock will be less efficient, highlighting a growing economic risk for mountain livestock farmers worldwide.